Method for recycling micro powder for MOA (Metal Oxide Arrester) piezoresistor ceramic

By testing and adjusting the dispersant and binding agent for MOA varistor ceramics, and adding defoaming agent and plasticizer during the granulation process, the molding problem caused by too fine particle size of the micropowder is solved, and efficient utilization of the micropowder is achieved, and the pass rate and product quality of the resistor sheet are improved.

CN119638449APending Publication Date: 2025-03-18XIAN XD ARRESTER CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411868183.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

During the production process of MOA varistor ceramics, the particle size of the fine powder separated by the cyclone separator of the granulation tower is too fine, resulting in problems such as large exhaust pressure and large mold release resistance during the molding process, affecting the quality of the resistor sheet and production continuity.

Method used

By testing the residual amount of dispersant and binding agent in the micro powder material for MOA varistor ceramics, the amount of addition to the slurry is adjusted, and defoaming agent and plasticizer are added during the granulation process, the granulation parameters are optimized to improve particle uniformity and fluidity.

Benefits of technology

It effectively reduces the waste of micro powder materials, improves the utilization rate of raw materials, avoids defects during molding, improves the pass rate of resistor sheets to more than 95%, and ensures the stability and consistency of product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638449A_ABST
    Figure CN119638449A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lightning arrester manufacturing, in particular to a method for recycling micro powder for MOA piezoresistor ceramics. The method comprises the following steps: S1) testing the residual amounts of a dispersing agent and a binding agent in the micro powder for the MOA piezoresistor ceramic, and respectively recording the residual amounts as x and y; s2) mixing the micro powder with water, a binding agent and a dispersing agent to obtain slurry; the mass ratio of the micro powder to the water to the binding agent to the dispersing agent is 4000: 2000: (600-y): (20-x); and S3) granulating the slurry until the slurry contains water, and molding to obtain the resistor disc. The method provided by the invention not only reduces the loss of the micro powder, but also improves the utilization rate of the raw materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of arrester manufacturing, and in particular to a method for recycling micro powder used in MOA varistor ceramics. Background Art

[0002] Granulation is an important process in the production of metal oxide arrester (MOA) varistor ceramics. The slurry is usually sprayed and granulated to form a granular material suitable for subsequent processing. Granulation is usually carried out in a granulation tower. Due to the large volume of the granulation tower, the humidity and pressure control in the granulation tower is very critical. A certain negative pressure needs to be maintained by an induced draft fan so that the wet air can be discharged out of the tower in time. However, this negative pressure environment will cause a large amount of granulation material powder to be extracted out of the tower. The loss of these powders accounts for about 1.9%. If they are discarded directly, on the one hand, the powders contain heavy metals such as Co and Ni, which will pollute the environment. On the other hand, the high price of heavy metals such as Co and Ni will lead to a large amount of waste of raw materials.

[0003] In order to solve the above problems, the fine powder separated by the cyclone separator of the granulation tower is currently collected and then subjected to subsequent processes such as moisture, aging, and molding. The fine powder separated by the cyclone separator accounts for about 1.6%. Based on a monthly feed of 75 tons, about 1.2 tons of fine powder can be recovered each month, and about 14 tons of fine powder can be recovered throughout the year. This method can effectively reduce the waste of raw materials and also reduce the production costs of enterprises.

[0004] However, the spray granulation material separated by the cyclone separator of the granulation tower is too fine, the micro powder is too much, the average particle size is small, and the fluidity of the granulation material is poor. If the micro powder is directly hydrated and aged before molding, problems such as high exhaust pressure and high demoulding resistance will occur during the molding process, which will cause the resistor to have multiple defects such as interlayer, cracking, bubbles, and small holes. The qualified rate of resistor production is about 50%, which affects the quality of the final resistor product and cannot be produced continuously and stably.

[0005] How to recycle and reuse the micro-powder produced in the production process of MOA varistor ceramics is an urgent problem that needs to be solved. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a method for recycling and reusing micro powder for MOA varistor ceramics.

[0007] To achieve the above object, the present invention provides a method for recycling and reusing micro powder for MOA varistor ceramics, comprising the following steps:

[0008] S1) Testing the residual amounts of dispersant and binder in the micro powder for MOA varistor ceramics, which are recorded as x and y respectively;

[0009] S2) mixing the above-mentioned fine powder with water, a binder and a dispersant to obtain a slurry; the mass ratio of the fine powder, water, a binder and a dispersant is 4000:2000:600-y:20-x;

[0010] S3) granulating the slurry, adding water, and molding it into a resistor sheet.

[0011] Optionally, the dispersant is selected from dispersant A15.

[0012] Optionally, the binder is selected from polyvinyl alcohol.

[0013] Optionally, the slurry also includes a defoaming agent.

[0014] Optionally, the defoaming agent is selected from one or more of defoaming agents BYK-019 and BYK-088.

[0015] Optionally, the mass ratio of the defoaming agent to the micropowder is 0.1-0.5:4000.

[0016] Optionally, the slurry also includes a plasticizer.

[0017] Optionally, the plasticizer is selected from PEG6000.

[0018] Optionally, the mass ratio of the plasticizer to the micropowder is 0.1-0.5:4000.

[0019] Optionally, the slurry includes: micro powder, water, binder, dispersant, defoamer and plasticizer;

[0020] The mass ratio of the micro powder, water, binder, dispersant, defoamer and plasticizer is 4000:2000:600-y:20-x:0.5:0.5.

[0021] Compared with the prior art, the present invention provides a method for recycling and reusing micro powder materials for MOA varistor ceramics. The method provided by the present invention not only reduces the loss of micro powder materials, but also improves the utilization rate of raw materials.

[0022] The present invention achieves at least the following beneficial effects:

[0023] 1. Effectively reduce the waste of micro powder: By improving the mixing and granulation process of micro powder slurry, the waste of micro powder can be effectively reduced. Compared with the existing technology, this technical solution can make more effective use of micro powder, thereby reducing the production cost of the enterprise. 2. Improve product quality: The present invention can avoid defects caused by the molding process by collecting and reusing micro powder and adjusting its components, and the product qualification rate reaches more than 95%, thereby improving the quality of the final product. Compared with the existing technology, the present invention can better ensure the quality stability and consistency of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a particle diagram of the micro powder material after treatment in Example 1;

[0025] Figure 2 This is a particle diagram of the micropowder obtained in Comparative Example 2. DETAILED DESCRIPTION

[0026] The present invention provides a method for recycling micro powder for MOA varistor ceramics, comprising the following steps:

[0027] S1) Testing the residual amounts of dispersant and binder in the micro powder for MOA varistor ceramics, which are recorded as x and y respectively;

[0028] S2) mixing the above-mentioned fine powder with water, a binder and a dispersant to obtain a slurry; the mass ratio of the fine powder, water, a binder and a dispersant is 4000:2000:600-y:20-x;

[0029] S3) granulating the slurry, adding water, and molding it into a resistor sheet.

[0030] The present invention does not specifically limit the method for detecting the residual amount of dispersant and binder in the micro-powder for MOA varistor ceramics in step S1), and can be a detection method known in the art, including but not limited to using thermal analysis equipment to detect the sampled micro-powder. The detection result can be used as a basis for accurately controlling the content of added organic matter (including binder, dispersant, etc.) when mixing the slurry.

[0031] In the micro powder material, the melting point of the dispersant is 110°C to 130°C; the melting point of the binder is 200°C to 250°C.

[0032] The x is preferably 1 to 2 parts by weight.

[0033] The above y is preferably 120 to 150 parts by weight.

[0034] According to the test results, the dosage of the binder and the dispersant is adjusted. The addition ratio of the micropowder, water, binder and dispersant is preferably 400:2000:(0-600):(0-20). Preferably, the mass ratio of the micropowder, water, binder and dispersant in the mixed slurry is 4000:2000:600:20.

[0035] The dispersant is preferably dispersant A15.

[0036] The binder is preferably polyvinyl alcohol.

[0037] The present invention tests the residual amounts of dispersants and binders in the micro-powder for MOA varistor ceramics, and can accurately adjust the amounts of dispersants and binders added in subsequent slurries, thereby improving the qualified rate of resistor sheets.

[0038] Preferably, the slurry also includes a defoaming agent.

[0039] The defoamer is preferably one or more of defoamers BYK-019 and BYK-088.

[0040] The mass ratio of the defoaming agent to the fine powder is preferably 0.1-0.5:4000, more preferably 0.5:4000.

[0041] Preferably, the slurry also includes a plasticizer.

[0042] The plasticizer is preferably PEG6000.

[0043] The mass ratio of the plasticizer to the fine powder is preferably 0.1-0.5:4000, more preferably 0.5:4000.

[0044] In some preferred embodiments of the present invention, the slurry comprises: micro powder, water, a binder, a dispersant, a defoamer and a plasticizer.

[0045] The mass ratio of the added amounts of the micro powder, water, binder, dispersant, defoamer and plasticizer is preferably 4000:2000:600-y:20-x:0.5:0.5.

[0046] The test results show that the addition of defoamers and plasticizers can adjust the viscosity range of the mixed slurry, effectively improve the lubricity and moisture retention of the micro-powder granulation material, reduce the defects of the formed green body, and help to further improve the qualified rate of the resistor, effectively solving the problems of uneven micro-powder particles, weak adhesion, and poor fluidity in the existing granulation process; and the problems of defects such as interlayers and cracks in the green body during the forming process. In addition, the above adjustment can also reduce the subsequent molding demolding resistance by adjusting the viscosity range of the slurry.

[0047] After the slurry is obtained, it can be granulated, hydrated, and formed into a resistor sheet.

[0048] The present invention has no particular limitation on the above-mentioned granulation, moisture-containing and molding methods, which can be any applicable method known to those skilled in the art.

[0049] The granulation is preferably spray granulation.

[0050] Preferably, the present invention uses a particle size analysis device to test the particle size distribution of the micro powder material, and further optimizes the spray granulation parameters during the granulation process, which can effectively increase the average particle size of the micro powder material and improve the fluidity of the granulated material.

[0051] The spray granulation parameters are preferably outlet temperature: 100±10°C; inlet temperature: 300±20°C; pump pressure: 2.0±0.1MPa.

[0052] The water content is specifically obtained by spraying the granulated powder with water. Preferably, the granulated powder is sprayed with water until the water content is about 1.2±0.1%.

[0053] The molding is specifically to dry-press the granulated powder containing water into a mold according to a conventional method.

[0054] The above method not only reduces the loss of micro powder, but also improves the utilization rate of raw materials.

[0055] In order to further illustrate the present invention, the following is a detailed description in conjunction with the embodiments. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.

[0056] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0057] Example 1

[0058] Step 1: Take samples and use particle size analysis equipment to test the particle size of the micro powder. Add the collected micro powder into the ball mill, add water, binder and dispersant, and the formula ratio is: 4000:2000:600:20. After the slurry is mixed, adjust the granulation parameters and then granulate, contain water, and form D45H24 resistors. 100 samples are formed. Granulation parameters are: outlet temperature: 100±10℃; inlet temperature: 300±20℃; pump pressure: 2.0±0.1MPa. Step 2: Sinter at 1100℃ according to the production process, and then carry out painting → grinding → aluminum spraying process, and finally conduct electrical performance testing.

[0059] The test results show that by testing the particle size of the micro powder with a particle size analysis device and then adjusting the spray granulation parameters, the particles obtained have better uniformity.

[0060] Figure 1 This is a picture of the micro powder particles after treatment in Example 1. It can be seen that the micro powder particles after treatment are more uniform.

[0061] Example 2

[0062] Step 1: Take a sample and use a thermal analysis device to test the residual amount of dispersant (A15) in the micro-powder, and the measured residual amount is 1g to 2g. Step 2: Add the collected micro-powder to a ball mill, add water, binder and dispersant, and the formula ratio is: 4000:2000:600:18. After the slurry is mixed, the granulation parameters are adjusted to granulate, contain water, and form D45H24 resistors, and 100 samples are formed. The granulation parameters are the same as in Example 1. Step 3: Firing at 1100°C according to the production process, followed by painting → grinding → aluminum spraying processes, and finally electrical performance testing.

[0063] Example 3

[0064] Step 1: Take samples and use thermal analysis equipment to test the residual amount of dispersant (A15) and binder (polyvinyl alcohol) in the micropowder. The residual amount of dispersant is 1g~2g, and the residual amount of binder is 120g~150g. Step 2: Add the collected micropowder to a ball mill, add water, binder and dispersant, and the formula ratio is: 4000:2000:450:18. After the slurry is mixed, the granulation parameters are adjusted to granulate, contain water, and form D45H24 resistors, and 100 samples are formed. The granulation parameters are the same as in Example 1. Step 3: Firing at 1100°C according to the production process, followed by painting → grinding → aluminum spraying processes, and finally electrical performance testing.

[0065] Comparative Example 1

[0066] Step 1: Prepare the collected micro powder, add water, and mold D45H24 resistors, and mold 100 samples. Step 2: Sinter at 1100℃ according to the production process, and then carry out the painting → grinding → aluminum spraying process, and finally conduct electrical performance testing.

[0067] Comparative Example 2

[0068] Step 1: Add the collected fine powder into the ball mill, add water, binder and dispersant, the formula ratio is: 4000:2000:600:20. After the slurry is mixed, it is granulated, hydrated, and molded into D45H24 resistors, and 100 samples are molded. Granulation parameters are: outlet temperature 100±10℃, inlet temperature 350±10℃, pump pressure: 2.0±0.1MPa. Step 2: Sinter at 1100℃ according to the production process, and then carry out painting → grinding → aluminum spraying process, and finally conduct electrical performance testing.

[0069] Figure 2 It is the particle diagram of the micro powder material in comparative example 2 without adjusting the granulation parameters.

[0070] The test results show that without performing a particle size test, the spray granulation parameters are different from those in Example 1, and the uniformity of the obtained particles is poor.

[0071] Example 4

[0072] Step 1: Take samples and use thermal analysis equipment to test the residual amount of dispersant (A15) and binder (polyvinyl alcohol) in the micropowder. The residual amount of dispersant is 1g~2g, and the residual amount of binder is 120g~150g. Step 2: Add the collected micropowder to a ball mill, and then add water, binder, dispersant and defoamer. The defoamer is BYK-019, and the formula ratio is: 4000:2000:450:18:0.5. After the slurry is mixed, the granulation parameters are adjusted, and then granulation, water inclusion, and molding of D45H24 resistors are carried out, and 100 samples are molded. The granulation parameters are the same as in Example 1. Step 3: Firing at 1100°C according to the production process, followed by painting → grinding → aluminum spraying process, and finally electrical performance testing.

[0073] Example 5

[0074] Step 1: Take samples and use thermal analysis equipment to test the residual amount of dispersant (A15) and binder (polyvinyl alcohol) in the micropowder. The residual amount of dispersant is 1g~2g, and the residual amount of binder is 120g~150g. Step 2: Add the collected micropowder to a ball mill, and then add water, binder, dispersant and defoamer. The defoamer is BYK-088, and the formula ratio is: 4000:2000:450:18:0.5. After the slurry is mixed, the granulation parameters are adjusted, and then granulation, water inclusion, and molding of D45H24 resistors are carried out, and 100 samples are molded. The granulation parameters are the same as in Example 1. Step 3: Firing at 1100°C according to the production process, followed by painting → grinding → aluminum spraying process, and finally electrical performance testing.

[0075] Example 6

[0076] Step 1: Take samples and use thermal analysis equipment to test the residual amount of dispersant (A15) and binder (polyvinyl alcohol) in the micropowder. The residual amount of dispersant is 1g~2g, and the residual amount of binder is 120g~150g. Step 2: Add the collected micropowder to a ball mill, and then add water, binder, dispersant, defoamer and plasticizer. BYK-019 is used as the defoamer, and PEG6000 is used as the plasticizer. The formula ratio is: 4000:2000:450:18:0.5:0.5. After the slurry is mixed, the granulation parameters are adjusted, and then granulation, water inclusion, and molding of D45H24 resistors are carried out, and 100 samples are molded. The granulation parameters are the same as in Example 1. Step 3: Firing at 1100°C according to the production process, followed by painting → grinding → aluminum spraying process, and finally electrical performance testing.

[0077] Example 7

[0078] Step 1: Take samples and use thermal analysis equipment to test the residual amount of dispersant (A15) and binder (polyvinyl alcohol) in the micropowder. The residual amount of dispersant is 1g~2g, and the residual amount of binder is 120g~150g. Step 2: Add the collected micropowder to a ball mill, and then add water, binder, dispersant, defoamer and plasticizer. BYK-088 is used as the defoamer, and PEG6000 is used as the plasticizer. The formula ratio is: 4000:2000:450:18:0.5:0.5. After the slurry is mixed, the granulation parameters are adjusted, and then granulation, water inclusion, and molding of D45H24 resistors are carried out, and 100 molded samples are formed. The granulation parameters are the same as in Example 1. Step 3: Firing at 1100°C according to the production process, followed by painting → grinding → aluminum spraying process, and finally electrical performance testing.

[0079] Comparative Example 3

[0080] Step 1: Take samples and use thermal analysis equipment to test the residual amount of dispersant (A15) and binder (polyvinyl alcohol) in the micropowder. The residual amount of dispersant is 1g~2g, and the residual amount of binder is 120g~150g. Step 2: Add the collected micropowder to a ball mill, add water, binder, dispersant and defoamer, and use tributyl phosphate as the defoamer, with a formula ratio of 4000:2000:450:18:0.5. After the slurry is mixed, adjust the granulation parameters and then granulate, contain water, and form D45H24 resistors, forming 100 samples. The granulation parameters are the same as in Example 1. Step 3: Firing at 1100°C according to the production process, followed by painting → grinding → aluminum spraying, and finally electrical performance testing.

[0081] Performance Testing

[0082] The inspection qualified rate of the resistors and the final product qualified rate obtained by the above method were counted, where the inspection qualified rate refers to the number of resistors that were subjected to electrical performance tests after forming, sintering, painting, grinding, and aluminum spraying. The results are shown in Table 1.

[0083] Table 1 Summary of product qualification rates of Examples 1 to 7 and Comparative Examples 1 to 3

[0084]

[0085] The above test results show that the invention greatly improves the product qualification rate by adjusting the addition amount of the binder and dispersant and further adding the defoamer and plasticizer, so that the product qualification rate can reach 99% to 100%.

[0086] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for recycling and reusing micro powder for MOA varistor ceramics, comprising the following steps: S1) Testing the residual amounts of dispersant and binder in the micro powder for MOA varistor ceramics, which are recorded as x and y respectively; S2) mixing the above-mentioned fine powder with water, a binder and a dispersant to obtain a slurry; the mass ratio of the fine powder, water, a binder and a dispersant is 4000:2000:600-y:20-x; S3) granulating the slurry, adding water, and molding it into a resistor sheet.

2. The method according to claim 1, characterized in that The dispersant is selected from dispersant A15.

3. The method according to claim 1, characterized in that: The binder is selected from polyvinyl alcohol.

4. The method according to claim 1, characterized in that The slurry also includes a defoaming agent.

5. The method according to claim 4, characterized in that The defoamer is selected from one or more of defoamers BYK-019 and BYK-088.

6. The method according to claim 4, characterized in that The mass ratio of the defoamer to the micro powder is 0.1-0.5:4000.

7. The method according to claim 1, characterized in that The slurry also includes a plasticizer.

8. The method according to claim 7, characterized in that The plasticizer is selected from PEG6000.

9. The method according to claim 7, characterized in that: The mass ratio of the plasticizer to the micro powder is 0.1-0.5:4000.

10. The method according to claim 1, characterized in that The slurry comprises: micro powder, water, binder, dispersant, defoamer and plasticizer; The mass ratio of the micro powder, water, binder, dispersant, defoamer and plasticizer is 4000:2000:600-y:20-x:0.5:0.5.

Citation Information

Cited By

  • Method for secondary recycling of alumina ceramic granulation material

    CN122853859A